Health benefit of zumba: their satisfaction and its impact on quality of life - Rozali, Muhammad Azrai; Soe, May Khin Soe (2017)
Recently there has been a trend in Zumba, a type of dance workout which incorporates music and bodily movement. Nevertheless, in terms of quality of life and satisfaction, the data is scarce. This questionnaire based cross sectional study is designed to assess relationship between Zumba players’ satisfaction score and quality life score. Questionnaires were distributed randomly to 100 Zumba players both gender at the local Zumba fitness centre from states of Pahang, Johor and Perak in 2016. The questionnaires consisted of 5 sections that measured satisfaction scores and quality of life. Quality of life score was calculated by finding the sum and average score of general health and perception. Majority of respondents were female, 74%. Amongst age categories, age group of 18-30 year dominates. A positive relationship was seen between number of times join Zumba and satisfaction score (F(2.96)=3.499), p=0.034). Furthermore, a trend was seen that as the numbers of times join Zumba increases so does the quality of life score, but it was not significant enough. Although a positive correlation was seen between Zumba and quality of life score, the relationship was weak. Low number of respondents and limited area of coverage might not truly reflect how Zumba has an impact in improving quality of life. Further studies need to be done and address these limitations to evaluate Zumba’s role in quality of life.